2013
DOI: 10.1111/jhq.12040
|View full text |Cite
|
Sign up to set email alerts
|

Completing the Audit Cycle: The Impact of an Electronic Reporting System on the Feedback Loop in Surgical Specialties

Abstract: Our intervention resulted in a considerable increase in the number of incidents reported, evaluated, and acted upon. Such an effect would be expected to improve patient safety, although further studies are needed to definitively confirm this. We therefore recommend the use of electronic systems and further studies to evaluate their impact on patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Given the literature regarding under-reporting [8,10,12,13], we believe that the increased reporting rate is more likely due to an increase in the willingness to report incidents, rather than simply an increase in actual incidents. The effect of increasing incident reports is widely expected to improve patient safety [7]. Our study shows evidence of improvements in knowledge of and attitude towards patient safety among nurses as a result of the current educational intervention.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Given the literature regarding under-reporting [8,10,12,13], we believe that the increased reporting rate is more likely due to an increase in the willingness to report incidents, rather than simply an increase in actual incidents. The effect of increasing incident reports is widely expected to improve patient safety [7]. Our study shows evidence of improvements in knowledge of and attitude towards patient safety among nurses as a result of the current educational intervention.…”
Section: Discussionmentioning
confidence: 51%
“…Other educational intervention studies have used several forms of intervention, such as newsletters and information pamphlets [7,14,15] or substantial education sessions (e.g., a plenary day) [17]. In our study, the short 15-minute education provided the information easily in an actual medical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations for increased reporting include using a standardized electronic reporting system and creating a culture that encourages leaders to view problems as opportunities for improvement rather than for punishment. Mandavia et al reported similar outcomes after implementing electronic reporting that resulted in a 198% increase in good catch reports.…”
Section: Discussionmentioning
confidence: 81%
“…To establish a culture of safety, leaders must eliminate behaviors that inhibit the reporting of errors and unsafe conditions while holding everyone responsible for adhering to safe practices . The electronic, rather than manual, tracking of incidents and good catches enables organizations to obtain timely and meaningful information that leaders can use to promote shared learning and prevent adverse events …”
Section: Review Of the Literaturementioning
confidence: 99%